An analysis of 1386 periurethral bulking procedures with comparison to 18, 763 retropubic tapes. Issue 2 (June 2020) - Bach, Fiona; Toozs-Hobson, Philip
Objective: To use British Society of Urogynaecology surgical database to evaluate periurethral bulking agents and retropubic tapes. Study design: Permission was granted to analyse 1386 periurethral bulking agents and 18, 763 retropubic tapes. The primary outcome measure was patient reported global impression of improvement for incontinence with secondary outcomes of change in symptoms of stress incontinence, overactive bladder and complications. Results: Patients undergoing periurethral bulking agents were older than retropubic tapes (mean 59.4 vs. 52.3 years). Urodynamic stress incontinence was the commonest urodynamic diagnosis (periurethral bulking agents 67%, retropubic tapes 77%) but there was a higher proportion of complex diagnoses in the periurethral bulking agents group. 59.2% patients reported 'very much/much better' on patient reported global impression of improvement for incontinence for periurethral bulking agents compared to 91% for retropubic tapes; 28% patients felt their symptoms of stress incontinence were cured following periurethral bulking agents compared to 77.6% for retropubic tapes and 0.8% developed de novo overactive bladder following periurethral bulking agents compared to 4% with retropubic tapes. There was no difference in outcomes when using periurethral bulking agents as a primary or secondary procedure. There were no intraoperative complications with periurethral bulking agents and fewer post-operative complications compared to retropubic tapes (3.6%). Conclusion: Patient reported success of periurethral bulking agents is lower than retropubic tapes but this is offset by minimal complications despite being an older, more complex patient group. Periurethral bulking agents do appear equally efficacious as a secondary procedure. Information derived from databases can be used during counselling to allow clinicians to demonstrate their own success and complication rates to ensure patients make an informed choice. Patient choice is paramount so all options should be included in full counselling.